2017
DOI: 10.1109/tbme.2017.2756870
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Characterizing Tonic Thermal Pain Across Subjects From EEG Data Using Random Forest Models

Abstract: Objective Effective pain assessment and management strategies are needed to better manage pain. In addition to self-report, an objective pain assessment system can provide a more complete picture of the neurophysiological basis for pain. In this study, a robust and accurate machine learning approach is developed to quantify tonic thermal pain across healthy subjects into a maximum of ten distinct classes. Methods A random forest model was trained to predict pain scores using time-frequency wavelet representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 60 publications
0
68
0
Order By: Relevance
“…The electrical biopotentials generated by the human body are signals commonly used in medical diagnosis. The main biopotentials are electrocardiagram (ECG) [82,85], electromyogram (EMG) [11,35,43,215] and electroencephalogram (EEG) [46,50,[216][217][218][219]. Biopotential sensors are usually composed of the following elements: electrodes, used for the transduction of the ionic signals inside the body to electrical signals; an analog conditioning stage for the amplification of the electrical signal, of very low intensity, at measurable levels avoiding electromagnetic interference (EMI); and an analog-digital conversion stage.…”
Section: Biopotentials For Pain Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrical biopotentials generated by the human body are signals commonly used in medical diagnosis. The main biopotentials are electrocardiagram (ECG) [82,85], electromyogram (EMG) [11,35,43,215] and electroencephalogram (EEG) [46,50,[216][217][218][219]. Biopotential sensors are usually composed of the following elements: electrodes, used for the transduction of the ionic signals inside the body to electrical signals; an analog conditioning stage for the amplification of the electrical signal, of very low intensity, at measurable levels avoiding electromagnetic interference (EMI); and an analog-digital conversion stage.…”
Section: Biopotentials For Pain Assessmentmentioning
confidence: 99%
“…Since EEG signals are very weak, the application of conductive gels can improve the quality of the signal by reducing the impedance of the electrode-skin contact [46]. EEG has numerous practical advantages, since it is a non-invasive technique, with high temporal resolution, provides relevant clinical information, is low-cost and requires little maintenance [50]. EEG studies have shown the activation of specific regions of the brain as a result of pain stimuli [216,217].…”
Section: Electroencelography and Chronic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows a summary of the previous studies on the classification of high pain and low pain caused by different types of pain stimulations, from different EEG analysis. Based on the information in Table 1, it is noticed that although some classification models have been developed, and high accuracy has been achieved using time-frequency representation of EEG signals for multiple classes of cold pain [16][17][18], none of the studies so far have achieved high classification accuracy from feature vector of pain-ERP for multiple pain perception levels. The reason may lie in the lack of the investigation on the component of classification, feature extraction and selection.…”
Section: Introductionmentioning
confidence: 99%